Karakteristik Pasien Pada Pemeriksaan Elektroneurografi di Rumah Sakit Universitas Mataram Provinsi Nusa Tenggara Barat Periode Januari 2020 Hingga Desember 2020 - ghalvan sahidu; Ilsa Hunaifi; Herpan Syafii Harahap; Decky Aditya Zulkarnaen (Unram Medical Journal, 2022)
Abstract Background: Electroneurography (ENG) is also known as nerve conduction examination, which includes examination of motor, sensory and slow response nerve conduction velocity (KHS). Abnormalities of KHS and evoked potentials may reveal the underlying pathophysiology of peripheral nerve disorders. With a good clinical examination, the ENMG examination will very helpfull main diagnosis. This examination helps determine the topical diagnosis, pathology and prognosis of peripheral nervous system disorders. Methods: This type of research is a descriptive observational study from the patient's medical record to determine the profile and results of the examination of patients undergoing electroneurography examination at the outpatient polyclinic, Mataram University Hospital. Sampling in the form of medical record data from January 1, 2020 - December 31, 2020 with a sample of 40 people. The research data will be entered and presented in tables and figures. Then the tables and figures will be analyzed. Results: Patients the most research subjects male as many as 27 people (67.5%). Patients who have the most body weight with a weight range of 51-100 kg 30 people (75%). For the highest height of the sample is in the range of 150-200 cm with a total of 34 people (85%). Most of the patients with non-traumatic complaints were 34 people (85%). The highest number of patients was polyneuropathy with a total of 22 people (55%). Conclusion: From this study, it was found that patients who take electroneurographic examinations at the Neurology Polyclinic at the University of Mataram had very varied characteristics and examination results.